Genetic influence on choroidal vascularity index - Je Moon Yoon; Yong Jin Gil; Joohon Sung; Don-Il Ham; Mingui Kong (PLoS ONE, 2025)
Purpose To investigate the heritability of genetic influence on macular choroidal vascularity index (CVI). Methods Total choroidal area (TCA), luminal area (LA), and CVI was measured using horizontal scan of spectral-domain optical coherence tomography with enhanced depth imaging in the 373 healthy twin participants. Characteristics of the participants were investigated, including age, sex, axial length, hypertension, diabetes, drinking habits, and smoking status. Univariate and subsequent multivariate regression analyses were performed to evaluate the associations of these factors with TCA, LA, and CVI. Results Patients who were older and had a higher intraocular pressure, higher diastolic blood pressure, and lower pulse pressure showed associations with lower CVI (p<0.001, p = 0.014, p = 0.005, and p = 0.015, respectively). The covariate-adjusted heritability (±standard error) of the CVI was 0.716 ± 0.091, and the heritabilities of the TCA and LA were 0.691 ± 0.089 and 0.634 ± 0.100, respectively. Conclusion The TCA, LA, and CVI are highly heritable.